Interfacial engineering of CuSe2/FeSe2 heterojunctions for water splitting: a pathway to high-performance hydrogen and oxygen evolution reactions - Kumari, Sandhyawasini; Pahra, Swapna; Tripathy, Amrita; Sumanth, N.; Lopez-Salas, Nieves; Tiwari, Santosh K.; Khan, Afaq Ahmad; Devi, Pooja; Santosh, M. S. (Nanoscale)
Enhanced bifunctional electrocatalysis via CuSe 2 /FeSe 2 heterojunctions for efficient water splitting was achieved.